Kewarganegaraan dan Kebijakan Pendidikan di Indonesia Tantangan bagi Anak-anak dengan Status Kewarganegaraan Tidak Jelas - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Auria Trisi Novi Ana; Ari Maulana Ramadhan; Luthfiah Luthfiah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Citizenship and education policies in Indonesia play a crucial role in determining children's rights and access to quality education. However, challenges arise when addressing children with unclear citizenship status, such as those born to parents without permanent citizenship or those caught in ambiguous legal situations. This abstract examines how the uncertainty of citizenship status affects the access to and quality of education for these children in Indonesia. The study highlights major issues faced, including limited access to formal schooling, lack of adequate official documentation, and legal instability that restricts educational rights. Additionally, it explores existing government policies and the challenges in implementing them concerning the protection of educational rights for children with unclear citizenship status. The findings reveal the need for more inclusive policy reforms and effective strategies to ensure that all children, regardless of citizenship status, can enjoy their right to quality education. The study suggests a more holistic, human rights-based approach to addressing these issues and advocates for enhanced collaboration between government agencies, civil society, and international organizations to develop sustainable solutions.